Anti-artifacts techniques for neural recording front-ends in closed-loop brain-machine interface ICs - Chen, Weijian; Liu, Xu; Wan, Peiyuan; Chen, Zhijie; Chen, Yi (Frontiers in Neuroscience, 2024)
In recent years, thanks to the development of integrated circuits, clinical medicine has witnessed significant advancements, enabling more efficient and intelligent treatment approaches. Particularly in the field of neuromedical, the utilization of brain-machine interfaces (BMI) has revolutionized the treatment of neurological diseases such as amyotrophic lateral sclerosis, cerebral palsy, stroke, or spinal cord injury. The BMI acquires neural signals via recording circuits and analyze them to regulate neural stimulator circuits for effective neurological treatment. However, traditional BMI designs, which are often isolated, have given way to closed-loop brain-machine interfaces (CL-BMI) as a contemporary development trend. CL-BMI offers increased integration and accelerated response speed, marking a significant leap forward in neuromedicine. Nonetheless, this advancement comes with its challenges, notably the stimulation artifacts (SA) problem inherent to the structural characteristics of CL-BMI, which poses significant challenges on the neural recording front-ends (NRFE) site. This paper aims to provide a comprehensive overview of technologies addressing artifacts in the NRFE site within CL-BMI. Topics covered will include: 1) understanding and assessing artifacts; 2) exploring the impact of artifacts on traditional neural recording front-ends; 3) reviewing recent technological advancements aimed at addressing artifact-related issues; 4) summarizing and classifying the aforementioned technologies, along with an analysis of future trends.